Assessment of Arsenic Toxicity and Tolerance Characteristics of Bean Plants (Phaseolus Vulgaris) Exposed to Different Species of Arsenic. (7th February 2018) - Chandra, Sukanya; Saha, Rajnarayan; Pal, Parimal
ABSTRACT: Experiments were conducted to evaluate the arsenic toxicity, its accumulation and phytoremediation potential of bean plants ( Phaseolus vulgaris ) grown in soils contaminated with different species of arsenic such as arsenite (As(III)), arsenate (As(V)) and dimethylarsinic acid (DMA). Bean plants were grown in soils amended by aqueous solutions of 20 and 50 mg kg −1 of As (III), As(V) or DMA. Arsenic species negatively affected the yield and growth of the plant. The study demonstrated arsenic accumulation in the plant parts. The concentration of arsenic compounds in the shoots decreased in the order arsenate > arsenite > dimethylarsinic acid while in the roots as arsenite > arsenate > dimethylarsinic acid. Most arsenic is accumulated in the roots with limited transfer to shoots. Thus, bean plants can be considered as an arsenic excluder and has the potential for phytostabilization of arsenic contaminated sites. The study also reveals that removal of arsenic by boiling the vegetables with excess of water is not possible.